2016
DOI: 10.1515/phys-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow and heat transfer over an unsteady stretching surface

Abstract: Abstract:In this paper we have studied the flow and heat transfer of a horizontal sheet in a viscous fluid. The stretching rate and temperature of the sheet vary with time. The governing equations for momentum and thermal energy are reduced to ordinary differential equations by means of similarity transformation. These equations are solved approximately by means of the Optimal Homotopy Asymptotic Method (OHAM) which provides us with a convenient way to control the convergence of approximation solutions and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 34 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…The analysis is interesting but it lacks the novelty enhanced heat transfer mechanism which has paramount importance for industrial and engineering purposes. Another study in this regard is reported in Elbashbeshy and Bazid 23 for nonpermeable surface which is actually a special case of the study presented in Ene 22 for conventional liquid. Therefore, the work published in 22 , 23 could be prolonged for the study of nanofluids which is the demand of modern world.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The analysis is interesting but it lacks the novelty enhanced heat transfer mechanism which has paramount importance for industrial and engineering purposes. Another study in this regard is reported in Elbashbeshy and Bazid 23 for nonpermeable surface which is actually a special case of the study presented in Ene 22 for conventional liquid. Therefore, the work published in 22 , 23 could be prolonged for the study of nanofluids which is the demand of modern world.…”
Section: Introductionmentioning
confidence: 88%
“…Another study in this regard is reported in Elbashbeshy and Bazid 23 for nonpermeable surface which is actually a special case of the study presented in Ene 22 for conventional liquid. Therefore, the work published in 22 , 23 could be prolonged for the study of nanofluids which is the demand of modern world. The main concerns of the study are to modify the existing models for nanofluids composed by ND and Ag nanoparticles and the comparison of thermal performance between them.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations